Germline variants in DNA repair genes are associated with young-onset head and neck cancer - Cury, Sarah Santiloni [UNESP]; Miranda, Priscila Mayrink de; Marchi, Fabio Albuquerque; Canto, Luisa Matos do; Chulam, Thiago Celestino; Petersen, Annabeth Høgh; Aagaard, Mads M.; Pinto, Clóvis Antonio Lopes; Kowalski, Luiz Paulo; Rogatto, Silvia Regina (Elsevier, 2021)
The genetic predisposition to head and neck carcinomas (HNSCC) and how the known risk factors (papillomavirus infection, alcohol, and tobacco consumption) contribute to the early-onset disease are barely explored. Although HNSCC at early onset is rare, its frequency is increasing in recent years. Germline and somatic variants were assessed to build a comprehensive genetic influence pattern in HNSCC predisposition and patient outcome. Whole-exome sequencing was performed in 45 oral and oropharynx carcinomas paired with normal samples of young adults (≤49 years). We found FANCG, CDKN2A, and TPP germline variants previously associated with HNSCC risk. At least one germline variant in DNA repair pathway genes was detected in 67% of cases. Germline and somatic variants (including copy number variations) in FAT1 gene were identified in 9 patients (20%) and 12 tumors (30%), respectively. Somatic variants were found in HNSCC associated genes, such as TP53, CDKN2A, and PIK3CA. To date, 55 of 521 cases from the large cohort of TCGA presented < 49 years old. A comparison between the somatic alterations of TCGA-HNSCC at early onset and our dataset revealed strong similarities. Protein-protein interaction analysis between somatic and germline altered genes revealed a central role of TP53. Altogether, germline alterations in DNA repair genes potentially contribute to an increased risk of developing HNSCC at early-onset, while FAT1 could impact the prognosis.
Keywords: Cancer predisposition; Early-onset cancer; Oral cavity carcinomas; Oropharynx carcinomas; Risk factors; Whole-exome sequencing